PENGINGKATAN KUALITAS IKAN KEMBUNG ASIN (Rastrelliger sp) DENGAN PENAMBAHAN CHITOSAN KULIT UDANG SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI DI SMA - Sri Wulandari; Elya Febrita; Irfan Andi Gafur (Biogenesis, 2017)
ABSTRACT  Do research on the effectiveness of the addition of chitosan mengetaui shells on the quality of salted mackerel (Rastrelliger sp) to draft a student worksheet that was conducted in April and May 2016. The study was carried out by two phases: the field research and resistant design student worksheet (LKS ). Research experiments were conducted using a completely randomized design (CRD) non factorial, consisting of 5 treatments and 3 replicates in order to obtain 15 units of the experimental design. The observed parameters including moisture content, protein content, fat content and organoleptic value which include appearance, aroma, taste and texture. The results showed that the addition of shrimp shell chitosan significant effect on water content, protein content and fat content in the salted mackerel (Rastrelliger sp). Where to lower the moisture content of up to 9.545%, fat content up to 1,543% and can also increase the protein content of up to 48.905%. While hendonik organoleptic test appearance and taste of the most favored panelist on the addition of 3% chitosan concentration, aroma on chitosan 2% and while the texture preferred chitosan panelist at 4%. Results from the study are used as a design student worksheet (LKS) on the subjects of biology in high school. Key words: Chitosan, Salted Mackerel Fish, Student Worksheet.